Introduction—Unruly Landscapes: Mobility, Transience, and Transformation. Issue 1 (1st March 2022) - Cisani, Margherita; Lo Presti, Laura; Pearce, Lynne; Peterle, Giada; Rabbiosi, Chiara
Abstract : In June 2020, the Centre for Mobilities Research (CeMoRe) at the University of Lancaster (UK) and the Centre for Advanced Studies in Mobility & Humanities (MoHu) at the University of Padua (Italy) co-hosted an international conference on the theme of "Unruly Landscapes." As a result of the pandemic, the two-day event had to be moved online, but participants nevertheless enjoyed two days of inspiring discussion as the speakers engaged with the intersection of landscape and mobility from a variety of disciplines and approaches. It was striking that this was a theme that attracted scholars from diverse scholarly and artistic communities, and we have attempted to reproduce the freshness of these dynamic, cross-disciplinary perspectives in the way we have grouped the articles here. Indeed, in order to maximize the diversity of the contributions. we sought approval from the Transfers editors to publish twelve shorter articles of 5, 000 words each across two special sections. We trust that readers of the journal will enjoy our purposefully "unruly" juxtaposition of disciplines and approaches, including the different ways that our contributors have understood and conceptualized the mobile landscape. However, both here and in our Introduction to Unruly Landscapes No. 2, we have sought to make sense of what is going on in each article and to indicate how it contributes to the recent debates that most interest readers of this journal. We would also like to take this opportunity to thank Professor Tim Ingold for his keynote lecture at the conference which spoke about his recent work on landscape as "palimpsest"—as well as artist Jen Southern (Lancaster University) for allowing us to use her formulation of the "unruly" for our event.